Book-tax conformity and earnings management: recent research - Floropoulos, Stylianos; Tsipouridou, Maria; Spathis, Charalambos (International Conference on Business and Economics - Hellenic Open University, 2023)
Corporations use two different sets of financial statements which have mirror-image goals, firms want to maximize book income reported to investors, while minimizing the taxable income reported to the tax authorities. The dual nature of corporate profit reporting may be creating a lose-lose situation, less meaningful profit numbers for capital markets and lowered corporate tax revenue for the government. Defenders of the book-tax divide argue that a unified system cannot accommodate these differing objectives, while supporters of the book-tax conformity claim that a tax-based book income can restore the integrity of the financial accounting system. The study reviews the arguments of high vs. low book-tax conformity. It also reviews prior research that examines the association between book-tax conformity and earnings management. JEL Classification: H2, M4, M40, M41 Key words: book-tax conformity, earnings management, book income, tax income, tax incentives